Improving Students Comprehension by Using Jigsaw Technique for the First Grade Students of SMA NU AL-Fudloli Ganjaran Gondanglegi Malang - Abrori, Ahmad; Sholah, Hanif Maulaniam (Jurnal Tinta, 2019)
Reading comprehension is the ability to analyze and understand the text in some reading context. This ability is taught to generalize the ability and share information in the reading context. In this research, the researcher applied Jigsaw Technique to solve the problems that were faced by the students. This research was conducted in order to improve students’ reading comprehension in descriptive text through Jigsaw Technique in the first grade students of SMA NU AL-FUDLOLI Ganjaran Gondanglegi Malang 2017-2018. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. The researcher conducted this research in two cycles. Each cycle consisted of three meetings. The researcher used Jigsaw Technique to make pleasant atmosphere during teaching and learning process of reading, and more importantly to improve the students’ reading comprehension especially on reading descriptive text. The subject of this research was the students of first grade students in SMA NU AL-FUDLOLI. The instruments to collect the data were interview, observation checklist, and reading test. The result of this research showed that by using Jigsaw Technique in teaching reading descriptive text, the researcher could improve the student’s reading comprehension especially descriptive text. Their responses showed that they were interested to learn reading subject because they felt easier to read using Jigsaw Technique. Based on the result of cycle 1 the average of their score is 67. The result of cycle 2, the average of their score is 76.